Comparative Analysis of Investment Efficiency Factors in Regional Industrial Development: Analisis Perbandingan Faktor Efisiensi Investasi dalam Pengembangan Industri Daerah - Hojikulova Feruza Dona kizi (Academia Open, 2025)
The research focuses on evaluating investment performance within Surkhandarya's regional industry sector along with its factors which promote industrial enterprise development and sustainability. The study establishes an essential position for investment efforts because they drive economic stability alongside employment growth and technological development. Research shows a considerable lack of information about how efficient investments impact enterprise numbers in regional economic settings. The research implements correlation and regression analysis through econometric modeling with statistical data spanning from 2010 until 2023. The research shows clear positive relations between investment amounts and the growth of industrial enterprises because every 1% investment growth results in 0.63% industrial enterprise expansion. A 1% increase in the labor force leads to additional 0.42% participation in the workforce according to study findings. The research findings demonstrate how investments focused on underdeveloped areas especially agriculture sector development projects lead to improved regional economic diversification. The research demonstrates that investment optimization through strategic distribution improves industrial development and requires data-based decision-making. Data-driven policy-making together with improved infrastructure and innovation-based funding and balanced sectoral funding must be used to enhance regional development and economic policies and investment management. The field requires more research into specific industrial investment effects together with improved econometrics to better capture external economic influences for complete understanding about regional industrial development investments. Highlights: Investment drives economic stability, employment, and industrial growth. Econometric analysis shows positive investment impact on enterprise expansion. Strategic, data-driven policies enhance regional industrial development. Key words: Regional industrial sector, GRP, investment efficiency, comparative models, investment factors